Discovery of some novel imines of 2-amino, 5-thio, 1,3,4-thiadiazole as mucomembranous protector. Synthesis, anti-oxidant activity and in silico PASS approach - Bijo Mathew; Jerad Suresh; S. Anbazhagan; N. Chidambaranathan (Journal of Saudi Chemical Society, 2016)
A series of some novel imines (6a–f) of 2-amino, 5-thio 1,3,4-thiadiazole connected to benzimidazole chalcones were prepared. The structures of the final imines were ascertained by IR, 1HNMR, mass and elemental analyses. Predicted activity spectra of all the final derivatives were determined in the category of mucomembranous protector nature with a Pa value more than 0.7. All the newly synthesized compounds were screened for their antiulcer activity in the pylorus-ligated rats. Free radical scavenging activity of all final derivatives was determined by DPPH method.Compounds 6e, 6a and 6b showed a percentage protection of (73.47, 72.17 and 70.43 at a dose of 10mg/kgb.w.) when compared to standard omeprazole (77.37%, 2mg/kgb.w.). Compounds 6e, 6a and 6b showed free radical scavenging activity with an IC50 of 0.32, 0.39 and 0.49mM respectively. Scanning of stomach specimens using electron microscope revealed that the mice treated with standard and synthetic derivatives had no injury observed in stomach mucosa, which is identical to that of the control animal. It has been concluded that ulcer healing properties of the imines are probably due to their antioxidant action.